Single-operator cholangioscopy for diagnosis of cholangioadenoma (bile duct adenoma) and its potential impact on surgical management - Eccles, John; Thiesen, Aducio; Sandha, Gurpal (Endoscopy International Open, 2018)
Background and study aims Cholangioadenoma is not recognized commonly and is often only diagnosed on surgical specimens. Direct per oral single-operator cholangioscopy (SOC) allows characterization of common bile duct (CBD) lesions through direct visualization and directed forceps biopsies with potential for impacting surgical management decisions. This is a retrospective review of all SOC cases diagnosed with cholangioadenoma. Patient demographics and outcomes were recorded. Three patients (all male), average age 68 years (range 62 – 76 years), were identified to have a cholangioadenoma. The clinical indication for SOC was deranged liver enzymes with a dilated CBD and a CBD abnormality identified on biliary imaging. The site of cholangioadenoma was proximal, mid and distal CBD, respectively. All patients had a successful SOC with targeted biopsy-proven diagnosis. One patient had a synchronous cholangiocarcinoma and underwent palliative stenting whereas the other two patients underwent appropriate curative resection based on cholangioadenoma location. We conclude that SOC is safe and effective for diagnosis of cholangioadenoma and has potential impact on decisions for surgical management.